QUANTIFICATION OF MIXING PROCESSES IN ORE-FORMING HYDROTHERMAL SYSTEMS BY COMBINATION OF STABLE ISOTOPE AND FLUID INCLUSION ANALYSES - Schwinn G.; Wagner T.; Baatartsogt B.; Markl G. (My University, 2006)
In the Schwarzwald area, southwest Germany, more than 400 hydrothermal veins hosting different gangue and ore mineral assemblages cross-cut the crystalline basement rocks. Many of the post-Variscan fluorite-barite-quartz veins are considered to have precipitated through mixing of a deep saline brine with meteoric, low salinity waters. This hypothesis was tested using carbon, sulfur, and oxygen isotope data of sulfides, sulfates and calcite, coupled with fluid inclusion studies. Primary hydrothermal calcites from the deposits show a positive correlation of their δ13C (V-PDB) and δ18O (V-SMOW) values, which range from -12 to -3‰ and from 12 to 18.5‰, respectively. Carbon and oxygen isotope compositions of paragenetically young, remobilized calcite types are shifted towards higher values and range from -12 to -1‰ and from 20 to 25‰, respectively. We developed an improved calculation procedure for modeling the covariation of carbon and oxygen isotopes in calcite resulting from mixing of two fluids with different isotopic compositions and total carbon concentrations. In our model, the carbon speciation in the two model fluid end-members and the fluid mixtures are calculated using a speciation and reaction path code. The carbon and oxygen isotope covariation of primary Schwarzwald calcites can effectively be modeled by a mixing trend of a deep saline brine and a meteoric, low salinity water. Sulfur isotope data of barites from 44 hydrothermal fluorite-barite-quartz veins vary from 9 to 18‰ (CDT), sulfide ore minerals show δ34S values between -14.4 and 2.9‰. Calculated sulfide-sulfate equilibrium temperatures are in the range between 300 and 350 °C. These temperatures differ significantly from the formation temperatures of 150 to 200 °C of most of the deposits as estimated from fluid inclusions, and are interpreted as preserved paleotemperatures of the deep aquifer. This assumption has been carefully checked against possible contamination of an equilibrated sulfide-sulfate system from the deep aquifer with sulfate from surface-derived sources, considering also the kinetics of the sulfide-sulfate isotope exchange. A combination of the S isotopic results with microthermometric fluid inclusion data and constraints on the temperature of the meteoric water was used to calculate mixing ratios of the two fluid end-members. The results indicate that mass fractions of the deep saline brine in the mixed fluid were between 0.5 and 0.75. Considering all geologic, geochemical and isotopic information, we propose that the majority of the post-Variscan hydrothermal veins in the Schwarzwald area were precipitated by district-scale mixing of a homogeneous deep saline brine with meteoric waters. © 2005 Elsevier Inc. All rights reserved.